Expert survey on real‐world data utilization and real‐world evidence generation for regulatory decision‐making in drug lifecycle in Korea - Hankil Lee; Hyeon‐Soo Ahn; Sol Kwon; Hye‐Young Kang; Euna Han (Wiley, 2024)
Abstract As the importance of utilizing real‐world data (RWD)/real‐world evidence (RWE) for supporting regulatory scientific decision‐making continues to grow, experiences and inputs from experts become crucial for developing a systematic and practice‐oriented plan for the use of fit‐for‐purpose RWD/RWE. This study aimed to survey relevant experts from government agencies, industries, and academia to identify prerequisites for the drug life cycle in Korea. The questionnaire comprised the following: (A) the definition and categories of RWD/RWE, (B) the suitability and feasibility of using RWD/RWE at each authorization stage by the types of RWD, and (C) the challenges and solutions for the use of RWD/RWE. A total of 46 respondents completed the online survey, with 89.1% of them having prior experience with RWD/RWE usage. A majority of respondents agreed that RWD can be obtained from various sources. Among these sources, the registry was the most suitable source. It is suitable to compensate for the limitations of randomized control trials and ensure quality in data collection. Though there was consensus among the respondents for the use of RWD/RWE in post‐marketing surveillance, the use of such data in new drug application (NDA) was disagreeable. Respondents considered it necessary to write a protocol in advance for RWD collection and RWE generation, for all RWD types. In conclusion, this study examined the perceptions of experts for RWD/RWE use at each approval stage of drugs. The results suggest that guidelines for the fit‐for‐purpose use of RWD/RWE should be developed via careful deliberation among experts in the future.